1998
DOI: 10.1016/s0005-2728(98)00013-9
|View full text |Cite
|
Sign up to set email alerts
|

The 9-kDa phosphoprotein of photosystem

Abstract: The chloroplast gene psbH encodes a 9-10 kDa thylakoid membrane protein (PSII-H) that is associated with photosystem II and is subject to light-dependent phosphorylation at a threonine residue located on the stromal side of the membrane. The function of PSII-H is not known, neither is it clear what regulatory role phosphorylation may play in the control of PSII activity. Using particle gun-mediated transformation, we have created chloroplast transformants of Chlamydomonas reinhardtii in which the synthesis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(14 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…In contrast to phosphorylation at Thr-2, modification of Thr-4 is highly sensitive to the ambient light conditions, being rapidly dephosphorylated when plants are placed in darkness. In the green alga Chlamydomonas reinhardtii, PsbH is essential for assembling PSII in thylakoids (36); psbH mutants have a PSII-deficient phenotype and lack a functional PSII complex (36,37). O'Connor et al (37) concluded from studies showing that C. reinhardtii strains expressing a PsbH mutant lacking Thr-2 (Thr-2 to Ala) behave as wild-type, that phosphorylation of PsbH may not be important for its function.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to phosphorylation at Thr-2, modification of Thr-4 is highly sensitive to the ambient light conditions, being rapidly dephosphorylated when plants are placed in darkness. In the green alga Chlamydomonas reinhardtii, PsbH is essential for assembling PSII in thylakoids (36); psbH mutants have a PSII-deficient phenotype and lack a functional PSII complex (36,37). O'Connor et al (37) concluded from studies showing that C. reinhardtii strains expressing a PsbH mutant lacking Thr-2 (Thr-2 to Ala) behave as wild-type, that phosphorylation of PsbH may not be important for its function.…”
Section: Resultsmentioning
confidence: 99%
“…In the green alga Chlamydomonas reinhardtii, PsbH is essential for assembling PSII in thylakoids (36); psbH mutants have a PSII-deficient phenotype and lack a functional PSII complex (36,37). O'Connor et al (37) concluded from studies showing that C. reinhardtii strains expressing a PsbH mutant lacking Thr-2 (Thr-2 to Ala) behave as wild-type, that phosphorylation of PsbH may not be important for its function. However, our finding of a second phosphorylation site in PsbH and the demonstration that modification of this site is light responsive in vivo reopens the role of phosphorylation in PsbH function.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, we also found T8 phosphorylation of PsbH was decreased upon palmella formation (Figure 9C and Table 3). However, a T2 knockdown mutant of PsbH in C. reinhardtii has similar phonotype of wild-type strains, indicating that T2 phosphorylation of PsbH probably doesn't affect its function (O'Connor et al, 1998). Besides, PSII protein VI is the beta subunit of cytochrome b559 essential for PSII assembly, whose increase would enhance the cyclic electron transport (CET) or in a side path of electron flow for protecting PSII from photoinhibition (Figure 9C and Table 1; Burda et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In higher plants and algae, it is also the region on the PsbH protein where reversible N-terminal phosphorylation occurs (47). Also of note is that the deletion of the psbH gene from Chlamydomonas reinhardtii inhibited the accumulation of PSII in the membrane (48,49) and led Summers et al (48) to conclude that perhaps the primary role of the PsbH protein was to facilitate PSII assembly/stability. Furthermore, according to the current structural model of PSII shown in Fig.…”
Section: Discussionmentioning
confidence: 99%